2016 22nd International Conference on Automation and Computing (ICAC) 2016
DOI: 10.1109/iconac.2016.7604898
|View full text |Cite
|
Sign up to set email alerts
|

Identifying the potential of human-robot collaboration in automotive assembly lines using a standardised work description

Abstract: Abstract-The increased availability of sensitive and compliant lightweight robots for use in assembly lines collaborating with the human promises significant improvements of different sociotechnical aspects of work. Workplaces can be reorganized to assign monotonous or unergonomic tasks to the robot. Also unproductive jobs currently done by the human can be minimized by an improved work distribution. Since there is only little experience with the new generation of collaborating robots, the implementation of wo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(7 citation statements)
references
References 17 publications
0
7
0
Order By: Relevance
“…However, the physical properties of components were not discussed, and the tasks categorization was limited to cable harnessing. Another methodology was presented by (Teiwes et al, 2016), assigning a score to various assembly tasks identified in MTM methods for automation. The scores were based on experimentation and were limited in application.…”
Section: Literature Reviewmentioning
confidence: 99%
“…However, the physical properties of components were not discussed, and the tasks categorization was limited to cable harnessing. Another methodology was presented by (Teiwes et al, 2016), assigning a score to various assembly tasks identified in MTM methods for automation. The scores were based on experimentation and were limited in application.…”
Section: Literature Reviewmentioning
confidence: 99%
“…On the other hand, human-robot interaction in the general sense is a study of robotic systems for use by or with humans which concern with understanding, designing, and evaluating robots [36]. In physical human-robot interaction, human safety is the main concern and must be considered when evaluating robot setups in a workspace [37]. This interaction is related to a form of communication whether the robots and humans are positioned near to each other or not.…”
Section: New Era Of Industrial Robotsmentioning
confidence: 99%
“…Vice versa, with RF ¼ 0 and CF ¼ 0, no task can be performed by the robot and in collaboration, respectively. To estimate the potential of robot deployment to single stations of an assembly line, Teiwes et al (2016) develop a procedure to estimate the automation potential of a given line balance and apply their study to an automotive assembly line. Using their scoring system, they find that the majority of stations reach low (around 20%) or medium potential (around 40%) for deployment of collaborative robots.…”
Section: Problem Settingmentioning
confidence: 99%